Teaching and learning practices for academic freedom - Sengupta, Enakshi; Blessinger, Patrick (Bingley, U.K. : Emerald Publishing Limited, 2020)
Although academic freedom in teaching and learning methods is crucial to a nation's growth, the concept comes with numerous misnomers and is subjected to much academic debate and doubt. This volume maps out how truth and intellectual integrity remain the fundamental principle on which the foundation of a university should be laid. Seeking to widen the frontiers of academic freedom, the authors serve up a diverse range of case studies and examples of real-life practice to encourage readers to recognize the importance of the academic freedom of faculty and students, and acknowledge this freedom as one of the main goals to be achieved by any university. Ultimately, the authors demonstrate that the autonomy to work freely remains the foremost criterion of success, that it is a pre-requisite to facilitating the advancement of knowledge and quality of research in any institution of higher education, and is to be encouraged and supported by the leadership teams within those institutions.
Prelims -- Part I: Practicing Academic Freedom -- Chapter 1: Introduction to Teaching and Learning Practices for Academic Freedom -- Chapter 2: From a Century of Defeats: The Slow Emergence of Academic Freedom from the Courts in the Early 20th Century -- Chapter 3: Robbed of Academic Freedom Imposition of a Coercive Attendance Policy on Students -- Chapter 4: Balancing the Freedom to Teach with the Freedom to Learn: The Critical Role of Assessment Professionals in Ensuring Educational Equity -- Chapter 5: Sustaining Academic Freedom in the Transition to Online Degrees -- Chapter 6: Academic Freedom and Freedom of Speech: The Assault of Vulnerability -- Chapter 7: The Iron Cage University -- Part II: Academic Freedom in Research -- Chapter 8: Universities as Institutions of Higher Education Between Formation and Research -- Chapter 9: With Swinish Phrase Soiling Their Addition: Epistemic Injustice, Academic Freedom, and the Shakespeare Authorship Question -- Chapter 10: A University Beyond Aid: The Challenge to the Academic Freedom and Success of Ghanaian Universities of Over-Reliance on Donor Funding -- Chapter 11: Research Ethics Committees and the Quest for Academic Freedom: An Example of Faculty Voices, Issues of Ownership of Personal Beliefs and Pedagogical Practices within Higher Education -- About the Authors -- Name Index -- Subject Index.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Academic freedom; Sex discrimination in education; Racism in education; Academic freedom -- Case studies; Education -- Higher; Colleges of further education